The political economy of digital ecosystems scenario planning for alternative futures - Kitsing, Meelis (Routledge studies in the economics of innovation, 2022)
The book connects political economy perspectives with scenario planning for mapping out future trajectories of digital ecosystems. The focus is purposefully on digital ecosystems as it encompasses economic, political and social contexts on a global, national and local level. The diversity of political economy approaches allows the author to explore alternative meanings of digital ecosystem development, which is particularly useful for envisioning alternative futures. Often visions about the future of digital ecosystems suffer from a lack of imagination and confirmation bias which is favorable to the extrapolation of current trends. A wide range of political economy perspectives applied through positivist theorizing in this book show different interpretations of developments in digital ecosystems. Scenario planning teams around the world have applied a collective imagination to show how future trajectories can be radically different from the current trends. The book outlines meta-scenarios for alternative futures of the political economy of digital ecosystems by reviewing and synthesizing work of foresight teams. These meta-scenarios served as insights for developing four scenarios for European digital ecosystems through the workshops with high level executives and experts. The scenarios identified the nature of EU cooperation and development of digital infrastructure as key drivers. These four scenarios developed in the workshops are further operationalized in specific context by exploring implications for Estonia as well as for the Chinese investments into the European platforms. This exercise shows how scenarios of digital ecosystems can be used for stress-testing decisions and strategies. Decision-makers, students, scholars and other stakeholders in wide range of industries ranging from academia to ride-sharing can use the scenarios for reframing different development trajectories and future-proofing their strategies. The scenarios can be further developed and modified for specific purposes and context as they are not written in stone"--